Special Issue of PPAP 2013: Preface - Abebe, Surafel; Arnaoudova, Venera; Eshkevari, Laleh; Sabane, Aminata; Wu, Wei (Electronic Communications of the EASST, 2014)
On the 5th of March, 2013, the first workshop on Patterns Promotion and Anti-patterns Prevention (PPAP 2013) took place in Genova, Italy. PPAP 2013 was co-located with the 17th European Conference on Software Maintenance and Reengineering (CSMR'2013), the premier European conference on the theory and practice of maintenance, reengineering and evolution of software systems. With the aim of promoting the application of patterns and prevent the spread of anti-patterns, the first objective of PPAP is to build a bridge between the different families of patterns and anti-patterns in software engineering.